2007
DOI: 10.1021/jf0721491
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Role of Polyphenol Oxidase and Peroxidase in Browning of Fresh-Cut Melon

Abstract: Polyphenol oxidase (PPO) and peroxidase (POD) were extracted from two different varieties of melon ( Cucumis melo L. cantalupensis cv. Charentais and C. melo L. inodorus cv. Amarillo) and characterized using reliable spectrophotometric methods. In both cases the enzymes followed Michaelis-Menten kinetics, showing different values of kinetics parameters between the two cultivars: K m = 7.18 +/- 0.70 mM ('Charentais') and 6.66 +/- 0.20 mM ('Amarillo') mM; V max = 7.93 +/- 0.35 units/min ('Charentais') and 13.82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
59
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 38 publications
13
59
3
Order By: Relevance
“…In the case of M. stellatus seaweed POD, the value obtained for E a (121.6 kJ/mol) was about half that obtained for grape POD (271.9 kJ/mol; Fortea et al, 2009), four times lower than those obtained for potato (478 kJ/mol) or carrot (480 kJ/mol) PODs (Anthon & Barrett, 2002), but was similar to that obtained for ''Amarillo'' melon (160 kJ/mol; Chisari et al, 2008), ''Charantais'' melon (86 kJ/mol; Chisari et al, 2008), pepper PODs (151 kJ/mol; Serrano-Martínez et al, 2008), ''Elsanta'' and ''Madame Moutot'' strawberry PODs (96 and 74 kJ/mol, respectively; Chisari et al, 2007). The range of temperatures required for the inactivation of M. stellatus seaweed POD was 30-50°C, similar to that required for pepper POD (30-60°C; Serrano-Martínez et al, 2008), but lower than that required for Crimson Seedless grape (60-80°C; Fortea et al, 2009), potato (67-85°C) and carrot (70-84°C) (Anthon & Barrett, 2002), strawberry (50-80°C; Chisari et al, 2007), and melon PODs (40-70°C; Chisari et al, 2008). These results indicated that M. stellatus seaweed POD is less thermostable than crimson seedless grape, strawberry, melon, potato and carrot PODs, but similar to pepper POD.…”
Section: Resultssupporting
confidence: 67%
“…In the case of M. stellatus seaweed POD, the value obtained for E a (121.6 kJ/mol) was about half that obtained for grape POD (271.9 kJ/mol; Fortea et al, 2009), four times lower than those obtained for potato (478 kJ/mol) or carrot (480 kJ/mol) PODs (Anthon & Barrett, 2002), but was similar to that obtained for ''Amarillo'' melon (160 kJ/mol; Chisari et al, 2008), ''Charantais'' melon (86 kJ/mol; Chisari et al, 2008), pepper PODs (151 kJ/mol; Serrano-Martínez et al, 2008), ''Elsanta'' and ''Madame Moutot'' strawberry PODs (96 and 74 kJ/mol, respectively; Chisari et al, 2007). The range of temperatures required for the inactivation of M. stellatus seaweed POD was 30-50°C, similar to that required for pepper POD (30-60°C; Serrano-Martínez et al, 2008), but lower than that required for Crimson Seedless grape (60-80°C; Fortea et al, 2009), potato (67-85°C) and carrot (70-84°C) (Anthon & Barrett, 2002), strawberry (50-80°C; Chisari et al, 2007), and melon PODs (40-70°C; Chisari et al, 2008). These results indicated that M. stellatus seaweed POD is less thermostable than crimson seedless grape, strawberry, melon, potato and carrot PODs, but similar to pepper POD.…”
Section: Resultssupporting
confidence: 67%
“…The temperature dependence of k was evaluated using the Arrhenius equation: Figure 3. Other activation parameters, namely, ΔG # (Gibbs free energy for enzyme inactivation), ΔH # (enthalpy change, a measure of the number of non-covalent bonds broken), and ΔS # (entropy change, a measure of net enzyme and solvent disorder), were calculated using the relationships given below as described previously (Forsyth et al 1999 (Chisari et al 2007a), but different from those for strawberries (Chisari et al 2007b).…”
Section: Resultsmentioning
confidence: 99%
“…Food Sci., 33, 2015(2): 109-117 doi: 10.17221/384/2014 upon any cell-damaging treatment, the enzyme may become exposed to substrates, leading to rapid oxidation of phenols (Chazarra et al 2001). There have been numerous studies on PPO from various sources, such as olives (Ünal et al 2011), bananas (Ünal 2007), melon (Chisari et al 2007a), and strawberries (Chisari et al 2007b). However, there are few studies regarding the role of loquat PPO (Ding et al 1998a;SellesMarchart et al 2006;Şener et al 2011ab), and no specific studies regarding the loquat cv.…”
mentioning
confidence: 99%
“…PPO extraction from Red Delicious apple [4,[15][16][17][18] Organic Apples (Red Delicious) were purchased from a green store with the purpose of avoiding the mixture of chemical substances present in conventional grown apples. In order to optimize the extraction process different conditions were assessed involving changes in: Triton X-100 concentration, pH, ionic strength and buffer composition.…”
Section: Protein Determinationmentioning
confidence: 99%
“…This enzymatic process lowers fruit quality, changing aspect, taste and nutritional characteristics [1].The major enzyme responsible for this damage is polyphenol oxidase (PPO), a metalloprotein with two Cu (II) in its active site, which are essential for its activity. In the presence of oxygen PPO oxidizes o-diphenols to quinones and leads to brown pigments ( Figure 1) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%